The Use of GIS in Financing: Analysis of European Projects - Otero Borges, Lisandra (2025)
Geographic Information Systems (GIS) are essential for integrating and analyzing geospatial data. This study examines projects funded by the European Commission that utilize these technologies between 2014 and 2027. Data collection was conducted using the Community Research and Development Information Service (CORDIS), a database providing access to information on projects funded by the European Commission's research and innovation programs. Projects from Horizon 2020 (2014-2020) and Horizon Europe (2021-2027) were gathered. A total of 232 projects addressing relevant topics were identified. Indicators were established for analysis, including the evolution of the number of projects over the years, participation by country, collaboration between institutions, and thematic areas. The results show an irregular growth in the number of projects. The countries with the highest participation in the projects are Italy (103 projects), Spain (96 projects), and the United Kingdom (86 projects). The roles of institutions within the projects vary, including coordination, participation, partnerships, collaboration, and third parties. The institutions with the highest number of projects are Chancellor Masters and Scholars of the University of Cambridge (15 projects) and the Spanish National Research Council (CSIC) (12 projects). The thematic analysis reveals that GIS is used in various fields, including Social Sciences and Humanities research. Documentary disciplines are not frequently present in the analyzed projects, which may represent an opportunity for future research.